Red Wax Scale, Ceroplastes rubens Maskell (Insecta: Homoptera: Coccidae) - G. W. Dekle (EDIS, 2002)
This document is EENY-237 (originally published as DPI Entomology Circular 115), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2001.